PENGARUH SALES GROWTH, CAPITAL INTENSITY DAN ENVIRONMENTAL SOCIAL AND GOVERNANCE (ESG) TERHADAP TAX AVOIDANCE - Nurjanah, Siti; Romadhina, Anggun Putri (LPPM Universitas Putera Batam, 2025)
This study aims to analyze the effect of sales growth, capital intensity and environmental social and governance on tax avoidance. The type of research used is a quantitative research method using secondary data, by analyzing company financial reports and sustainability reports of companies in the manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2022. The sample used in this research was 9 companies using a purposive sampling technique.The panel data regression model was used as the research methodology in this study. Analysis of research results using the Eviews 12. The research results show that the best model is the Common Effect Model (CEM). The results of this research show that Sales Growth partially influences tax avoidance, Capital Intensity partially influences tax avoidance, Environmental social and governance has no influence on tax avoidance and simultaneously sales growth, capital intensity and Environmental social and governance influence tax avoidance.